Differences in birth weight between immigrants' and natives' children in Europe and Australia: a LifeCycle comparative observational cohort study. Issue 3 (23rd March 2023) - Florian, Sandra; Ichou, Mathieu; Panico, Lidia; Pinel-Jacquemin, Stéphanie; Vrijkotte, Tanja G M; Harskamp-van Ginkel, Margreet W; Huang, Rae-Chi; Carson, Jennie; Rodriguez, Loreto Santa Marina; Subiza-Pérez, Mikel; Vrijheid, Martine; Fernández-Barrés, Sílvia; et al.
Abstract : Objective: Research on adults has identified an immigrant health advantage, known as the 'immigrant health paradox', by which migrants exhibit better health outcomes than natives. Is this health advantage transferred from parents to children in the form of higher birth weight relative to children of natives? Setting: Western Europe and Australia. Participants: We use data from nine birth cohorts participating in the LifeCycle Project, including five studies with large samples of immigrants' children: Etude Longitudinale Française depuis l'Enfance—France (N=12 494), the Raine Study—Australia (N=2283), Born in Bradford—UK (N=4132), Amsterdam Born Children and their Development study—Netherlands (N=4030) and the Generation R study—Netherlands (N=4877). We include male and female babies born to immigrant and native parents. Primary and secondary outcome measures: The primary outcome is birth weight measured in grams. Different specifications were tested: birth weight as a continuous variable including all births (DV1), the same variable but excluding babies born with over 4500 g (DV2), low birth weight as a 0–1 binary variable (1=birth weight below 2500 g) (DV3). Results using these three measures were similar, only results using DV1 are presented. Parental migration status is measured in four categories: both parents natives, both born abroad, only mother born abroad and only father born abroad. Results: Two patterns in children's birth weight by parental migration status emerged: higher birth weight among children of immigrants in France (+12 g, p<0.10) and Australia (+40 g, p<0.10) and lower birth weight among children of immigrants in the UK (−82 g, p<0.05) and the Netherlands (−80 g and −73 g, p<0.001) compared with natives' children. Smoking during pregnancy emerged as a mechanism explaining some of the birth weight gaps between children of immigrants and natives. Conclusion: The immigrant health advantage is not universally transferred to children in the form of higher birth weight in all host countries. Further research should investigate whether this cross-national variation is due to differences in immigrant communities, social and healthcare contexts across host countries.